The Impact of Change in Interest Rates and Fluctuation in Oil Prices on the Performance of the U.S. Stock Market Indices - Mohammed , Anas; Yamin, Ismail Younes (Journal of Ecohumanism, 2024)
This study aims to determine the impact of changes in interest rates and oil price fluctuations on the performance of the main U.S. stock market indices (Dow Jones, Standard & Poor's 500, and Nasdaq). The study period included monthly data for the variables from (2010 to 2022). The study used (Autoregressive Distributed Lag -ARDL) To test short- and long-term relationships between study variables. The study reached several results, most notably the presence of a negative impact of changes in interest rates on the performance of US stock market indices in the short term, and a negative impact on the Nasdaq index in the long term, as well as the presence of a positive impact of oil price fluctuations on stock indices in the short and long term, and this is due to that United States economy is closely linked to the energy and oil sectors. Considering the study’s findings, it recommended the importance of investors benefiting from periods of rising interest rates by increasing investment in stocks in anticipation of a positive response to the market and an increase in its indicators in the medium and long term. It also recommended that investors take oil price fluctuations into consideration when making investment decisions in stocks, as rising oil prices tend to have a positive impact on indices, especially in the long term.